Research on service-driven network technologies for space-air-ground-sea integration - FAN Kexin; AN Lirong; ZHANG Qinyu (Dianxin kexue)
Facing the emerging novel applications and service demands, space-air-ground-sea integrated network offers advantages such as global coverage, high efficiency, flexibility, elasticity, and reliability. It provides intelligent, collaborative, and efficient ubiquitous information services for diverse service scenarios in many fields, and is an important part of future mobile communication system. Firstly, the domestic and international development status, network architecture, demands, and challenges of space-air-ground-sea integration were analyzed. Then, driven by the demand for carrying massive diverse services, key network technologies, including network slicing, mobile edge computing, and communication-sensing-computing integration, were investigated. Finally, the future development direction of space-air-ground-sea integration was discussed from the perspectives of intelligence, integration, and security.